Empowering Education: Pre-Service Training Analysis for Teacher Apprentice Professionalism in the 21st Century - ‘Alam, Ghasa Faraasyatul; Puspitaningsih, Arin Ika; Kusuma, Hanif Aulia; Anggana, Syeh Umar; Ramadhan, Sany Putra; Dewi, Tantri Kusuma (Journal of Education for Sustainability and Diversity, 2025)
The purpose of this research is empowering education with analyze pre-service training to realize and improve teachers apprentice professionalism in the 21st century. Research method used is quantitative with IBM SPSS Statistics 22 software. Respondents were taken from students who were active at Faculty of Computer Science, Brawijaya University. Total number of respondents reached 160 apprentice teachers. Steps include research process, research problem, literature review, research questions, research design, quantitative design with surveys, sampling, instruments, data analysis, interpretation, conclusions, and future research. Results include: (a) 26% usability of features integrated with training topics; (b) 24% convenience of interacting with the user interface in training; (c) 25% accuracy in selecting training materials according to needs; and (d) 25% interesting of interactive multimedia-based training interactions. Improvement in the quality of apprentice teachers can be seen from their professional performance by conducting regular training efforts that are tailored to current needs of 21st century educators.